Pelatihan Parenting Melalui Pemanfaatan Internet Sehat Sebagai Upaya Mereduksi Kecanduan Media Sosial Pada Remaja - Fitri Annisa, Dona; Pahlevi, Reza; Fatimah, Siti; Okta Sari, Resti (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2022)
The influence of social media greatly affects the growth and development of personality in adolescents. The family is the initial environment for adolescents who have a strategic role in providing control over the prevention of addiction to social media in adolescents. Therefore, an understanding of the importance of parenting through the use of healthy internet is needed to reduce internet addiction in adolescents, as well as provide education related to prevention of addiction to social media in adolescents. This training activity was held for students of SMA Darul Falah Cihampelas, West Bandung Regency. The method of implementing the activity is to provide education related to the use of healthy internet as an effort to reduce social media addiction in adolescents.